PLACEMAKING RUANG JALAN KORIDOR KOMERSIAL KOTA SURAKARTA - Patrani Victorya T; Rizon Pamardhi Utomo; Galing Yudana (Universitas Sebelas Maret Surakarta, 2016)
Placemaking is an attempt to form a space into a place that has meaning for its users. The concept of placemaking motivated by all the existing space in the city, both of street and public space that can have meaning as a place where it will occur at the site of social interaction and communication among users of space. Street in a commercial corridor in Surakarta is an important infrastructure to support commercial activities, but the function of the cause of street becomes passive and less interested in the community to conduct joint activities in that space. This shows that street is still not able to accommodate other activities simultaneously and social interactions that lead to placemaking. The problem in this study is whether placemaking already happening commercial corridor street and how much street placemaking commercial corridors. Scope of this research include the way to commercial corridor Surakarta with sample corridor commercial there are six . The method used to determine how much placemaking happened in the commercial corridor of street to be reviewed based on variables derived from placemaking elements, namely comfort and image, accessibility and linkage, uses and activities, as well as sosialibility. The research proves that placemaking has occurred in the commercial corridor of street in Surakarta. But the realization of placemaking in commercial corridor street is still weak, as indicated by the lack of availability of means of supporting activities in the form sitting group. Pedestrian walkway used for informal traders activity and social interaction has not been evenly occurs in the entirety of the commercial corridors in the city of Surakarta. Keywords: placemaking, street, commercial corridor.